Stora Tullhuset; Gothenburg's new waterfront market and cultural hub Stora Tullhuset; Gothenburg's new waterfront market and cultural hub - Farhat Hussaini, Shakiba; Typa, Eleftheria (My University, 2026)
Stora Tullhuset is an old customs house located along the Göta River in central Gothenburg. After Casino Cosmopol closed in 2024, the building has been largely empty. It holds both architectural and historical value, but today it feels disconnected from the city around it. The surrounding spaces are fragmented, public access is limited, and its links to the waterfront and the wider city have weakened over time. This thesis looks at how a building like Stora Tullhuset can be brought back to life in a way that serves the pub lic and meets today´s environmental and social needs. The goal of the project is to design a proposal that turns Stora Tullhuset into a cultural hub for architecture and design, with a public food and market hall on the ground floor. The aim is to bring people back to the site, strengthen the connection between the building and the river, and show how an existing structure can be reused rather than replaced. The study looks at the building´s structure, its history, and the surrounding water. The work involved archi tectural intervention, spatial reorganization, and cli mate adaptation within a sustainable design framework. The design process included literature studies, analysis of historical drawings, interviews with Higab AB, the property owner, and Canea, a tenant in the building, as well as case study comparisons and ongoing design de velopment. Regular site visits helped assess conditions such as daylight, wind, noise, pedestrian movement, traffic, and land use. The project draws on theories of adaptive reuse, public space, and sustainability by Plevoets and Van Cleempoel , Gehl, Bullen and Love , Douglas, and Haggman. The result is a design that reopens the inner courtyard, brings in a mix of cultural and market uses, and in cludes flood proofing strategies to prepare for future water risks. The ground floor is redesigned as an open public space that connects the city to the water. By combining good spatial design, a variety of uses, and climate adaptation, the proposal places Stora Tullhuset back at the heart of Gothenburg’s waterfront; as an active, resilient, and sustainable civic building.
Keywords: Building transformation - Adaptive reuse - Public space reactivation - Sustainable design